Challenges and Inequalities of Opportunities in European Psychiatry Research: The Example of Psychodiagnostic Tool Availability in Research on Early Autism Identification - Bolte, Sven; Tomalski, P.; Marschik, P.; Berggren, S.; Norberg, J.; Falck-Ytter, T.; Pokorska, O.; Jones, E.; Charman, T.; Roeyers, H.; Kostrzewa, E. (Hogrefe Publishing, 2016)
© 2016 Hogrefe Publishing. Europe is diverse in terms of economy, cultures, socio-demography, and languages. A crucial aspect of psychiatric research is the availability of standardized screening, diagnostic, and characterization instruments. We fine-mapped the accessibility of 14 clinical scales and cognitive tests for the assessment of early childhood Autism Spectrum Disorder (ASD; e.g., ADOS, ADI-R, SCQ, SRS, CHAT, MESL) within 21 European countries. These tools are essential for internationally com petitive early ASD detection research. We identified a considerable variation not only in the availability, but also psychometric standardization, and formal distribution of the instruments between the countries, privileging English speaking, high-income, and highly populated European countries. Absence of country-specific standardization was a problem across many countries, independent of income and size. Findings demonstrate, on a concrete level, the challenges in creating equal early ASD identification research opportunities in Europe, and the need for increased funding for instrument development and validation. We discuss the reasons, implications, and consequences of this inequity and ways of reducing it.